Sensory structures of the antennae of Nannotrigona testaceicornis (Apidae : Meliponinae) - Stort, A. C.; Moraes-Alves, MMB (New York Entomological Soc Inc, 1998)
The total number and distribution per antennal flagellomere of sensilla placodea (olfactory disks), sensilla coeloconica, sensilla ampullacea and sensilla campaniformia were determined in workers of Nannotrigona testaceicornis Lepeletier a stingless bee species quite common in Brazil. The distribution of the sensilla was uniform, with the largest number occurring in flagellomere 10 and gradually decreasing in the direction of the basal flagellomeres in a way similar to that observed in Scaptotrigona postica Latreille.Nannotrigona testaceicornis had a larger number of sensilla ampullacea and a smaller number of sensilla coeloconica and sensilla campaniformia than Scaptotrigona postica. Although Nan notrigona testaceicornis does not communicate through the formation of pheromone trails, this species presents a larger quantity of sensilla placodea (relative to the length of the flagellum) than Scaptotrigona postica.